Corporate social responsibility (CSR) in Vietnam: A conceptual framework - Nguyen Minh; Jo Bensemann; Stephen Kelly (International Journal of Corporate Social Responsibility (JCSR), 2018)
As the phenomenon of corporate social responsibility (CSR) establishes itself more globally, the question arises as to the nature of CSR in developing countries. Vietnam is one example of a developing country undergoing rapid economic growth coupled with societal challenges, driven by increased business activity. To date, however, there is a dearth of context-sensitive research on CSR in Vietnam, while the distinct political, economic, social and cultural context makes Vietnam an appropriate environment for critiquing the relevance of universal CSR theories in a local context. This paper provides a critical review of the peculiarities of the Vietnamese context, and proposes a conceptual framework consisting of three specific institutional level factors that potentially influence the nature of CSR in Vietnam. These contextual factors include tradition, political governance and modernity. In addition to emphasizing the context in which CSR is conceptualized and practiced, this paper also builds a theoretical foundation that aids in the development of CSR debates, in particular the parameters influencing CSR conceptualizations (CSR Thinking) and the implementation of CSR (CSR Doing) in Vietnam.
Keywords: 650; Corporate social responsibility; Vietnam; Conceptual framework; Context; National-level institutions